Operational Excellence and Commercial Banking Performance: A Competitive Advantage Opportunity - Muazu, Muazu Hassan; Hassan Nashehu, Hauwau (Journal of Technology Management and Business, 2021)
Commercial banks in the emerging markets have witnessed transformations in recent times, which has affected their operational performance. These transformations include consolidations, recapitalisation, technological advancement, compliance, and the rise in retail banking patronage. The increasing number of customers has become one of the sources of challenges to the banks. Other issues are challenges of effective service delivery, rise in the cost of operations, and branch network. Operational excellence is viewed as a strategy and a competitive advantage opportunity for overcoming some of these challenges as practised in other sectors of the economy in Nigeria and beyond. This paper adopted a case study approach to point out some of the opportunities and benefits derivable from operational excellence to the commercial banking operations in developing countries as experienced by banks in some developed nations. Also highlighted are some of the levers and approaches to implementing operational excellence in the banking sector. The article thus concludes that operational excellence improves banks' service delivery, customer satisfaction, cost-effectiveness and efficiency, a substantial increase in revenue and profit, and offers a competitive advantage to banks. Hence, Nigerian banks must leverage their workforce, processes, innovation, and governance to attain excellence in their operations for them to remain competitive in both regional and international markets.